Development of antibody-linked probes for characterisation of Pseudomonas associated with spoilage - Johnson, Sharon Maureen (2000)
The growth of micro-organisms in foods is different from that in axenic liquid culture in laboratory media. In natural environments, including food, micro-organisms generally grow in mixed culture and in close proximity to each other, because of which antagonistic or synergistic interactions can occur. To elucidate the behaviour of bacteria within food matrices an understanding of the food structure is required, as foods are complex ecosystems on the micrometer scale. Most processed foods are emulsions and as such are highly structured heterogeneous environments. Antibody-linked probes can be used for the immuno-location of micro-organisms or their products within food matrices to demonstrate the sites at which growth occurs and elucidate the possible bacterial interactions with food components. The aim of the project was to raise antibodies to spoilage Pseudomonas species and to use the developed antibody-linked probes to follow psychrotrophic spoilage Pseudomonas within heterogeneous foods. By using antibody-linked probes the natural spoilage of milk and milk products can be followed along traditional lines examining extrinsic parameters but with the additional benefit that the major spoilage organisms can be located within the mixed natural flora. The use of antibodies in this way facilitated the study of a defined natural population and surmounted any adaptive problems associated with introduced organisms. An oil-in-water near-foodgrade model was developed to investigate the growth of Pseudomonas as it overcame some of the technical problems of using natural cream. Pseudomonas species, which grew as colonies within the near-food-grade model, were visualised using fluorescently-labeled antibody-linked probes. Pseudomonas used to raise the antisera were isolated from psychrotrophically spoiled food and characterised together with isolates retrieved from the environment. The phenotypic characterisation of Pseudomonas using classical biochemical tests and API 20NE test strips (BioMerieux) did not produce definitive identifications of the unknown isolates. Nutritional screening of the Pseudomonas isolates using commercially produced standardised test microtitration plates (Biolog MicroPlate TM), that contained 95 carbon sources, was carried out. The data produced from the test microtitration plates were analysed using numerical taxonomic methods. The relatedness of the Pseudomonas isolates was strongly influenced by the source from which the test isolates originated and did not definitively identify all of the unknown isolates tested. Molecular techniques, ribotyping and amplified ribosomal DNA restriction analysis (ARDRA), based on the genomic fingerprinting of the 16S rRNA gene were evaluated to aid the definitive identification of the Pseudomonas isolates but needed a more extensive data base to be useful. The difficulties encountered in phenotypically identifying food and environmentally isolated Pseudomonas species stems from the fact that the Pseudomonas genus is now classified according to its ribosomal DNA homology. The classification of the species within the Pseudomonas genus is still under review. Robust phenotypic criteria for the identification of all the species within the genus have not to date been defined. In this study, the association of phenotype with environmental source of isolation (whether characterised by nutritional studies or by antibody cross-reaction) demonstrates clearly that more appropriate phenotypic characterisation is required to allow identification schemes to reflect the underlying phylogeny of this group.